Effectiveness of Lockdown in Reducing the Spread of COVID-19 (Indian Journal of Forensic Medicine & Toxicology, 2021)
At the end of 2019, a mysterious outbreak appeared, forming an atypical pneumonia suspected of originatingfrom an animal market in Wuhan China. The outbreak is a new type of coronavirus which is named asCOVID-19 disease (2019 – nCoV, Novel Coronavirus). COVID 19 disease is a viral infection caused bySARS-CoV-2, namely the acute respiratory syndrome coronavirus 2 which emerged in Wuhan, China.Vaccines and antiviral drugs have not been found, meanwhile COVID-19 are prevented by using nonpharmacologicalinterventions, one of the actions taken by several countries is to create policy protocolssuch as lockdowns.The results of this study indicate that lockdown is effective in reducing the spread of COVID -19, it can beseen from the significant decrease in R0 and Rt,
Keywords: Effectiveness, COVID-19, Lockdown, Spread, R0, Rt